2016
DOI: 10.2967/jnumed.115.167445
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide-1 Receptor PET/CT with 68Ga-NOTA-Exendin-4 for Detecting Localized Insulinoma: A Prospective Cohort Study

Abstract: Preoperative localization of insulinoma is a clinical dilemma. We aimed to investigate whether glucagon-like peptide-1 receptor (GLP-1R) PET/CT with 68Ga-NOTA-MAL-cys40-exendin-4 (68Ga-NOTA-exendin-4) is efficient in detecting insulinoma. Methods In our prospective cohort study, patients with endogenous hyperinsulinemic hypoglycemia were enrolled. CT, MRI, endoscopic ultrasound, and 99mTc-hydrazinonicotinamide-TOC SPECT/CT were done according to standard protocols. GLP-1R PET/CT was performed 30–60 min after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
137
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(146 citation statements)
references
References 32 publications
5
137
0
4
Order By: Relevance
“…GLP1 analogs have recently been shown to possess great sensitivity in the detection of insulinomas (20,21). Furthermore, in a prospective multicentric study conducted by Christ et al,using 111 In-diethylenetriaminepentaacetic acid-exendin-4 for single-photon-emission CT examination, a transient exacerbation of hypoglycemia was reported (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GLP1 analogs have recently been shown to possess great sensitivity in the detection of insulinomas (20,21). Furthermore, in a prospective multicentric study conducted by Christ et al,using 111 In-diethylenetriaminepentaacetic acid-exendin-4 for single-photon-emission CT examination, a transient exacerbation of hypoglycemia was reported (20).…”
Section: Discussionmentioning
confidence: 99%
“…A large, prospective cohort study by Luo et al, using 68 Galabeled exendin-4 derivative, also showed promising sensitivity for PET/CT when compared to other imaging modalities. High uptake in the kidneys, however, necessitated further imaging 2 to 3 h after injection in some cases (21).…”
Section: Discussionmentioning
confidence: 99%
“…6 Recently updated scatter correction protocols have reduced this problem, but if observed it can be resolved through re-processing PET data without use of 'scatter correction'.…”
mentioning
confidence: 99%
“…6 GLP1 negative cases are typically avid on SSTR imaging. 5,6 Halo reconstruction artefact (i.e. suppression of background activity adjacent to regions of intense uptake) is a known limitation of PET 'scatter correction' algorithms.…”
mentioning
confidence: 99%
“…Recent studies have shown that radiolabeled somatostatin receptor antagonists are preferable to agonists for in vivo peptide receptor targeting, and there are several ongoing studies across various NETs. Glucagon-like peptide-1 receptor imaging using 68 Ga-exendin-4 PET/CT (15) and 18 F-radiolabeled analogs of exendin-4 PET/CT has emerged and is highly sensitive for detecting benign insulinomas that might be missed by other imaging studies (16). Studies have also shown a high expression of C-X-C chemokine receptor type 4 in normal adrenal cortex and adrenocortical tumors, opening new avenues for imaging these tumors with peptides targeting C-X-C chemokine receptor type 4 ( 68 Ga-pentixafor) and theranostic approaches (17,18).…”
mentioning
confidence: 99%